Lysophosphatidic Acid Receptor 3 Promotes Mitochondrial Homeostasis against Oxidative Stress: Potential Therapeutic Approaches for Hutchinson-Gilford Progeria Syndrome - Jui-Chung Chiang; Wei-Min Chen; Ciara Newman; Benjamin P. C. Chen; Hsinyu Lee (MDPI AG, 2022)
Lysophosphatidic acid (LPA) is a growth factor-like lipid mediator that regulates various physiological functions via activation of multiple LPA G protein-coupled receptors. We previously reported that LPA suppresses oxidative stress in premature aging Hutchinson-Gilford progeria syndrome (HGPS) patient fibroblasts via its type 3 receptor (LPA3). Mitochondria have been suggested to be the primary origin of oxidative stress via the overproduction of reactive oxygen species (ROS). Mitochondria are responsible for producing ATP through oxidative phosphorylation (OXPHOS) and have a calcium buffering capacity for the cell. Defects in mitochondria will lead to declined antioxidant capacity and cell apoptosis. Therefore, we aim to demonstrate the regulatory role of LPA3 in mitochondrial homeostasis. siRNA-mediated depletion of LPA3 leads to the depolarization of mitochondrial potential (ΔΨm) and cellular ROS accumulation. In addition, the depletion of LPA3 enhances cisplatin-induced cytochrome C releasing. This indicates that LPA3 is essential to suppress the mitochondrial apoptosis pathway. LPA3 is also shown to improve mitochondrial ADP-ATP exchange by enhancing the protein level of ANT2. On the other hand, LPA3 regulates calcium uptake from the ER to mitochondria via the IP3R1-VDAC1 channel. Moreover, activation of LPA3 by selective agonist OMPT rescues mitochondrial homeostasis of H2O2-induced oxidative stress cells and HGPS patient fibroblasts by improving mitochondrial ΔΨm and OXPHOS. In summary, our findings imply that LPA3 acts as the gatekeeper for mitochondrial healthiness to maintain cell youth. Furthermore, LPA3 can be a promising therapeutic target to prevent mitochondrial oxidative stress in aging and HGPS.